Bacteriological Spectrum and Drug Resistance Among Patients Associated With Bloodstream Infection in Intensive Care Units in the Affiliated Hospital of Jiaxing University From 2021 to 2023 - Yucheng Xie; Xiaochun Tan; Wei Wang; Bailong Hou; Minjie Mao; Xiaoqin Niu; Qinlong Yu; Weifeng Shen (Canadian Journal of Infectious Diseases and Medical Microbiology)
Bloodstream infections (BSI) in ICU settings are associated with high morbidity, mortality, and healthcare costs. The ICU environment, with its high use of invasive devices and immunocompromised patients, fosters an increased risk for multidrug resistance (MDR) pathogens, complicating treatment strategies. Understanding the epidemiology and resistance patterns in these settings is essential for improving patient outcomes and guiding appropriate antimicrobial stewardship practices. This study retrospectively analyzed data from 640 blood culture samples collected in the ICU of the Affiliated Hospital of Jiaxing University between January 2021 and December 2023. The blood samples were appropriately collected and cultured. Matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry was employed to identify the isolated strains. Antimicrobial sensitivity was assessed using the VITEK2 system, the Epsilometer test (E-test), and the Kirby–Bauer disk diffusion method. All statistical analyses were conducted using IBM SPSS Statistics 22.0. A total of 391 bacterial pathogens (61.1%) were isolated. The predominant pathogens causing BSI were Gram-negative bacteria. The most prevalent pathogens during the period were coagulase-negative Staphylococci (CoNS, 17.1%), followed by Klebsiella pneumoniae (K. pneumoniae, 13.6%), Enterococcus spp (13.6%), Escherichia coli (E. coli, 12.3%), Acinetobacter baumannii (A. baumannii, 8.4%), and Staphylococcus aureus (S. aureus, 5.1%). Among the antibiotics tested, tigecycline, linezolid, vancomycin, and quinupristin/dalfopristin were effective against Staphylococci and Enterococci, although some CoNS strains exhibited resistance to vancomycin. Tigecycline showed effectiveness against the main gram-negative bacteria. Furthermore, multiple hospitalizations, comorbidity with diabetes, and the use of a central venous catheter were identified as significant risk factors for multidrug-resistant organisms (MDROs) in BSI cases. Pathogens isolated from the bloodstream of ICU patients exhibited significant drug resistance. We recommend strategies to mitigate the incidence of MDROs in BSI, including limiting the duration of hospital stays, closely monitoring underlying patient conditions, improving discharge plans, and strengthening transitional care, and prevent infections associated with central venous catheters.